2007
DOI: 10.1080/09540120701351888
|View full text |Cite
|
Sign up to set email alerts
|

The impact of illicit drug use and substance abuse treatment on adherence to HAART

Abstract: High levels of adherence to highly active antiretroviral therapy (HAART) are essential for virologic suppression and longer survival in patients with HIV. We examined the effects of substance abuse treatment, current versus former substance use, and hazardous/binge drinking on adherence to HAART. During 2003, 659 HIV patients on HAART in primary care were interviewed. Adherence was defined as ≥95% adherence to all antiretroviral medications. Current substance users used illicit drugs and/or hazardous/binge dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 23 publications
2
46
0
4
Order By: Relevance
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…20 Although there is scant literature on the association of substance abuse with primary care or gynecological appointment adherence, several studies examining the HIV-infected population in general have linked such factors as substance abuse to HIV medication nonadherence. [28][29][30][31] One study of 150 HIV-infected people found that drug use was associated with a 4-fold greater risk of medication adherence failure. 32 Unfortunately substance use and abuse in women is closely linked to HIV: the CDC reported that 1 in 5 new HIV diagnoses in women were related to injection drug use in 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Illicit drug use in HIV-infected patients can be linked to impairment of physical and mental health, low access to care, low health-related quality of life, suboptimal adherence to HIV treatment and poorer health outcomes than other HIV risk groups [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%